Elliptische Konstruktionen im gesprochenen Deutsch in der Talk-Show als Textsorte - Rybszleger, Paweł (Wydawnictwo Naukowe UAM, 2009)
The aim of this publication is to describe elliptical structures in spoken German language. The author focuses on the characteristics of medial talks, such as talk show, and concentrates on various elements of spoken language, such as anacoluthon, parenthesis or other forms of syntactic discontinuity. According to the Ethnomethodological Approach each communication forms a certain sociological order; it is organized and single statements depend on context. Ellipsis is one of syntactic elements of so called “Language economy”. Thanks to those elements speakers concentrate on delivering the most important contents in their speech.
Elliptical constructions in spoken German in the text type talk show
Keywords: Język niemiecki; Język potoczny; Talk show